In Vitro Accuracy of Two Different Electronic Apex Locators Under Various Conditions - Lucija Koturić Čabraja; Walter Dukić (Applied Sciences, 2025)
Background: The purpose of this study was to analyze the accuracy of two apex locators using seven different canal irrigants. Methods: Forty multi-rooted extracted teeth were included in this study. The actual canal length (ACL) was determined using a #10 file until the tip was visualized (12× magnification) just within the apical foramen (AF). The teeth were placed in a conductive medium of alginate to test the ACL and electronic canal length (ECL) using both apex locators in various conditions. Seven irrigant solutions were used in the root canal: 0.9% saline, FileEZE EDTA 19%, Glyde EDTA 17%, Consepsis V Chlorhexidine 2% CHX, Chlorcid 3%, citric acid 20%, and EDTA 18%. Results: Within a range of ±0.5 mm from the ACL, Raypex showed an accuracy of 87.5% with 0.9% saline solution, 82.5% with Chlorcid 3%, and 75% with Consepsis V CHX 2% solution. The Ipex showed an accuracy of 82.5% with 0.9% saline solution, 80% with Chlorcid 3%, and 70% with Consepsis V CHX 2% solution. The differences among the canal irrigants were significant for both the Raypex (p = 0.021) and Ipex (p < 0.0001) devices. The mean values showed the greatest variations in ECL accuracy with the combination of Raypex and EDTA 18% (p = 0.042) and with the Ipex and Glyde EDTA 17% (p = 0.026). Conclusions: Canal irrigants have an impact on the accuracy of apex locators. The apex locators showed an accuracy of 80% and greater when 0.9% saline and Chlorcid 3% solutions were used.